GNSS-, Communication-and Map-Based Control System for Initiation of a Heterogeneous Rendezvous Maneuver. Issue 3 (2016) - Reiter, Matthias; Abel, Dirk; Rofalski, Stefan; Moormann, Dieter
Abstract: This paper demonstrates a GNSS-(Global Navigation Satellite System), communication-and map-based control system initiating a heterogeneous rendezvous maneuver between a car-like ground vehicle and a fixed-wing aircraft. The rendezvous maneuver is intended to serve as a preparation step for an autonomous landing of the aircraft on the moving ground vehicle. The long term motivation is amongst others found in energy saving potentials seen in the use of ground-based takeoff and landing (TOL) support systems. For experimental validation, model-scale vehicles are used. While the ground vehicle itself could be seen a scaled version of a larger ground vehicle with similar 2-dimensional actuation capabilities, it is also intended to be used as a mock-up for a track-based MAGLEV system, a system often proposed in literature for ground-based TOL support systems. In order to mimic the behavior of a MAGLEV track, a Virtual Track application is implemented on the ground vehicle. Within the presented setup, the set-speed of the aircraft following predefined waypoints is fixed. At the same time, the longitudinal dynamics of the ground vehicle are used to synchronize it to the aircraft. The setup proposed in this paper incorporates the use of a digital map through which synchronization is assisted and automation capabilities are extended. Experimental results are shown to evaluate the possibilities of the proposed system.